CLASSIFICATION AND ZONING OF WATER QUALITY FOR THREE MAIN RIVERS IN BINH TRI THIEN REGION (CENTRAL VIETNAM) BASED ON WATER QUALITY INDEX - Nguyen Van Hop; Thuy Chau To; Truong Quy Tung (ASEAN Journal on Science and Technology for Development, 2008)
Huong, Thach Han and Kien Giang rivers are the important surface water sources in Thua ThienHue, Quang Tri and Quang Binh provinces, respectively (in Central Vietnam). The river water samples were taken monthly (from June 2001 to May 2002 for Kien Giang river and from January to December of 2004 for Thach Han and Huong rivers) at selected sites. The temperature, pH, conductivity (EC), salinity, turbidity (TUR), DO, COD, BOD5, nitrate, ammonia, phosphate, total solids (TS), hardness, total dissolved iron, total coliform (TC), fecal coliform (FC) and sodium adsorption ratio (SAR) of water samples were analyzed. Water quality index developed by Bhargava (Bhargava-WQI) was modified and applied to assess water quality of the above mentioned rivers. Based on Bhargava-WQI, the classification and zoning of the rivers for beneficial uses were carried out. The results obtained show that the water quality index can be used as an efficient tool for the water quality management and water pollution control of the rivers.